determine the exactness and obtain the general solutions.
1. (π₯ + π¦2 )ππ₯ + (2π₯π¦ + π¦2)ππ¦ = 0
2. (2π₯π¦3 + π₯2 )ππ₯ + (3π₯2π¦2 + π¦)ππ¦ = 0
3. (π2y + π₯)ππ₯ + (2π₯π2y + 1)ππ¦ = 0Β
Let us determine the exactness and obtain the general solutions.
1. Consider the equation "(\ud835\udc65 + \ud835\udc66^2 )\ud835\udc51\ud835\udc65 + (2\ud835\udc65\ud835\udc66 + \ud835\udc66^2)\ud835\udc51\ud835\udc66 = 0". Since "\\frac{{\\partial (x+y^2)}}{\\partial y}=2y=\\frac{{\\partial (2xy+y^2)}}{\\partial x}," we conclude that the differential equation is exact. Then "\\frac{{\\partial U}}{\\partial x}=x+y^2, \\frac{{\\partial U}}{\\partial y}=2xy+y^2." It follows that "U=\\frac{x^2}2+y^2x+C(y)," and hence "\\frac{{\\partial U}}{\\partial y}=2yx+C'(y)=2xy+y^2." Therefore, "C'(y)=y^2," and thus "C(y)=\\frac{y^3}3+C." We conclude that the general solution of the differential equation is "\\frac{x^2}2+y^2x+\\frac{y^3}3=C."
2. Consider the equation "(2\ud835\udc65\ud835\udc66^3 + \ud835\udc65^2 )\ud835\udc51\ud835\udc65 + (3\ud835\udc65^2\ud835\udc66^2 + \ud835\udc66)\ud835\udc51\ud835\udc66 = 0". Since "\\frac{{\\partial (2\ud835\udc65\ud835\udc66^3 + \ud835\udc65^2)}}{\\partial y}=6xy^2=\\frac{{\\partial (3\ud835\udc65^2\ud835\udc66^2 + \ud835\udc66)}}{\\partial x}," we conclude that the differential equation is exact. Then "\\frac{{\\partial U}}{\\partial x}=2\ud835\udc65\ud835\udc66^3 + \ud835\udc65^2, \\frac{{\\partial U}}{\\partial y}=3\ud835\udc65^2\ud835\udc66^2 + \ud835\udc66." It follows that "U=x^2y^3+\\frac{x^3}3+C(y)," and hence "\\frac{{\\partial U}}{\\partial y}=3x^2y^2+C'(y)=3x^2y^2+y." Therefore, "C'(y)=y," and thus "C(y)=\\frac{y^2}2+C." We conclude that the general solution of the differential equation is "x^2y^3+\\frac{x^3}3+\\frac{y^2}2=C."
3. Consider the equation "(\ud835\udc52^{2y} + \ud835\udc65)\ud835\udc51\ud835\udc65 + (2\ud835\udc65\ud835\udc52^{2y} + 1)\ud835\udc51\ud835\udc66 = 0". Since "\\frac{{\\partial (\ud835\udc52^{2y} + \ud835\udc65)}}{\\partial y}=2e^{2y}=\\frac{{\\partial (2\ud835\udc65\ud835\udc52^{2y} + 1)}}{\\partial x}," we conclude that the differential equation is exact. Then "\\frac{{\\partial U}}{\\partial x}=\ud835\udc52^{2y} + \ud835\udc65, \\frac{{\\partial U}}{\\partial y}=2\ud835\udc65\ud835\udc52^{2y} + 1." It follows that "U=xe^{2y}+\\frac{x^2}2+C(y)," and hence "\\frac{{\\partial U}}{\\partial y}=2xe^{2y}+C'(y)=2xe^{2y}+1." Therefore, "C'(y)=1," and thus "C(y)=y+C." We conclude that the general solution of the differential equation is "xe^{2y}+\\frac{x^2}2+y=C."
Comments
Leave a comment